PERTANGGUNGJAWABAN HUKUM PESERTA TENDER DAN PENYELENGGARA DALAM PRAKTIK PERSEKONGKOLAN PENGADAAN JASA KONSTRUKSI - Heriyanto Heriyanto; Abd. Rahman Saleh; Nova Diana Kholida (Fakultas Ilmu Sosial dan Humaniora, 2025)
Bid-rigging in the procurement of construction services is a practice that undermines the principles of fair competition and results in losses for service users as well as the state. This collusion often involves multiple parties, including tender participants and organizers, raising questions regarding their legal liability. This study aims to analyze the characteristics of tender collusion, the legal responsibilities of participants and organizers, and to examine the role of decisions issued by the Indonesian Competition Commission (KPPU) as an instrument of law enforcement. Using a normative juridical approach combined with case studies of KPPU decisions, the research reveals that tender collusion may take horizontal, vertical, or combined forms, all of which violate fair competition principles. Legal liability for participants and organizers may include administrative, civil, and criminal sanctions. Furthermore, KPPU decisions serve a strategic role in providing legal certainty, deterrence, and in reinforcing a culture of fair competition in the construction services sector.